KEPADATAN OPTIMUM IKAN MAS KOKI KOMET (Carassius auratus auratus) PADA SISTEM PENGANGKUTAN TERTUTUP - , RAYMON RAHMANOV ZEDTA, Dr. Ir. Triyanto, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the optimum density of comet goldfish (Carassius auratus auratus) in the closed transportation system for 12 hours. Experimental method in this study used completely randomized design (CRD) which consists of 5 treatments (7, 12, 17, 22, and 27 fish/L) with 3 replications. The average weight of comet goldfish was 5 Â± 0.5 g/fish obtained from Kediri, East Java. The results showed no mortality during the transportation. At the end of the adaptation of comet goldfish density of 7 fish/L had the highest survival rate is 96.82%, and a density of 27 fish/L had the lowest survival rate is 44.44%. Results showed that there were significant difference (P <0.05) between treatments in the adaptation period. The response relationship between the density and survival rate showed that higher density is lower the survival rate. The density of comet gold fish that produce highest survival rate was 7 fish/L, however based on technical or efficiency considertions in the transportation then the optimum density of of comet goldfish is 22 fish/L on the closed system transortation